Anatomy, pollen, and chromosomes of adenoa (turneraceae), a monotypic genus endemic to Cuba - González, Ana María (2012)
Fil: González, Ana María. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.